Exploring the Perceptions of Students with Different Learning Styles on Learning Vocabulary by Using Hello English Application - Miftahul Jannatus Sholihah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores the perceptions of students with different learning styles: visual, auditory, and kinesthetic towards the use of the Hello English application in learning English vocabulary. The background of this research is based on the growing role of technology in education, especially in the era of the Industrial Revolution 4.0, which has shifted many traditional learning methods into digital forms. Hello English is one of the educational applications that offers interactive and flexible features and can be accessed anytime and anywhere. However, only a few studies have examined how the application aligns with students’ individual learning styles. Therefore, this research aims to fill that gap by investigating how students with different learning styles perceive the application in their vocabulary learning process. This research employed a qualitative descriptive design. Three students from a junior high school in Jember were selected as participants through the VAK (Visual, Auditory, Kinesthetic) learning style test, with one student representing each learning style. The data were collected through semi-structured interviews and analyzed using Thematic Analysis as proposed by Braun and Clarke. The analysis revealed five major themes: awareness of learning styles, social learning preferences, the suitability of the application’s features, the strengths and weaknesses of the application, and students’ vocabulary learning strategies. The findings showed that most students were already aware of their learning styles before the research, and this awareness helped them choose more effective learning strategies. All participants preferred learning with others either with teachers or peers rather than learning independently, as they felt more comfortable and understood the material more easily. The application’s features were found to be suitable for each learning style. Visual learners appreciated the use of colors and layout, auditory learners benefited from the pronunciation features, and kinesthetic learners enjoyed the interactive games and sentence-building tasks. Although the application was generally perceived as effective, several weaknesses were identified. An auditory learner noted that not all materials had audio support, while kinesthetic learner mentioned that certain materials were too text-heavy and less engaging. Meanwhile, visual learner stated that the application had no drawbacks. The study concludes that Hello English is a helpful application that can support vocabulary learning for various types of learners. However, improvements are still needed, especially in terms of providing more audio content and physical interaction for kinesthetic learners. These findings highlight the importance of recognizing students’ learning styles when designing and implementing digital learning tools. As a result, applications like Hello English can be even more effective when combined with collaborative learning approaches that suit students’ preferences and needs.
Reupload file repositori 02 Feb 2026_Maya
Keywords: Vocabulary